CHALLENGES OF ENGLISH TEACHER IN THE PRACTICE OF HYBRID LEARNING IN THE 21ST CENTURY - Rachmat Cholif; Tri Kurniawati; Sahrawi Sahrawi (IKIP PGRI Pontianak, 2023)
This research is motivated by the researcher’s interest in EFL teachers at SMA N 1 Pemangkat using Hybrid Learning model. The purpose of this study is to describe the challenges faced by English teachers at SMAN 1 Pemangkat in the practice of hybrid learning in the 21st century. This research method uses descriptive qualitative. Interview and documentation are research tools used in this study. Interview as the main tool to collect data and information from informants. After that, documentation is concrete evidence used by the researcher to support data collections are RPP, Schedule of subjects, recordings, and photographs. The technique of sample selected is Saturation Sampling. The subjects of this study were English teachers at SMAN 1 Pemangkat. The result of this research is that there are challenges faced by English teachers in the hybrid learning model, namely; (1) The learning information does not arrive from the teacher to the students, (2) the teacher has difficulty in building the character and abilities of the students, and (3) the learning targets expected by the teacher are not achieved.Keywords: Hybrid Learning, Challenges of English Teacher, 21st Century